Dendrimers Target the Ischemic Lesion in Rodent and Primate Models of Nonarteritic Anterior Ischemic Optic Neuropathy. - Yan Guo; Mary A Johnson; Zara Mehrabian; Manoj K Mishra; Rangaramanujam Kannan; Neil R Miller; Steven L Bernstein (PLoS ONE, 2016)
INTRODUCTION:Polyamidoamine dendrimer nanoparticles (~ 4 nanometers) are inert polymers that can be linked to biologically active compounds. These dendrimers selectively target and accumulate in inflammatory cells upon systemic administration. Dendrimer-linked compounds enable sustained release of therapeutic compounds directly at the site of damage. The purpose of this study was to determine if dendrimers can be used to target the optic nerve (ON) ischemic lesion in our rodent and nonhuman primate models of nonarteritic anterior ischemic optic neuropathy (NAION), a disease affecting >10,000 individuals in the US annually, and for which there currently is no effective treatment. METHODS:NAION was induced in male Long-Evans rats (rNAION) and in one adult male rhesus monkey (pNAION) using previously described procedures. Dendrimers were covalently linked to near-infrared cyanine-5 fluorescent dye (D-Cy5) and injected both intravitreally and systemically (in the rats) or just systemically (in the monkey) to evaluate D-Cy5 tissue accumulation in the eye and optic nerve following induction of NAION. RESULTS:Following NAION induction, Cy-5 dendrimers selectively accumulated in astrocytes and circulating macrophages. Systemic dendrimer administration provided the best penetration of the ON lesion site when injected shortly after induction. Systemic administration 1 day post-induction in the pNAION model gave localization similar to that seen in the rats. CONCLUSIONS:Dendrimers selectively target the ischemic ON lesion after induction of both rNAION and pNAION. Systemic nanoparticle-linked therapeutics thus may provide a powerful, targeted and safe approach to NAION treatment by providing sustained and focused treatment of the cells directly affected by ischemia.